Fabrication of Core-Shell PEI/pBMP2-PLGA Electrospun Scaffold for Gene Delivery to Periodontal Ligament Stem Cells - Qiao Xie; Lie-ni Jia; Hong-yu Xu; Xiang-gang Hu; Wei Wang; Jun Jia (Stem Cells International)
Bone tissue engineering is the most promising technology for enhancing bone regeneration. Scaffolds loaded with osteogenic factors improve the therapeutic effect. In this study, the bioactive PEI (polyethylenimine)/pBMP2- (bone morphogenetic protein-2 plasmid-) PLGA (poly(D, L-lactic-co-glycolic acid)) core-shell scaffolds were prepared using coaxial electrospinning for a controlled gene delivery to hPDLSCs (human periodontal ligament stem cells). The pBMP2 was encapsulated in the PEI phase as a core and PLGA was employed to control pBMP2 release as a shell. First, the scaffold characterization and mechanical properties were evaluated. Then the gene release behavior was analyzed. Our results showed that pBMP2 was released at high levels in the first few days, with a continuous release behavior in the next 28 days. At the same time, PEI/pBMP2 showed high transfection efficiency. Moreover, the core-shell electrospun scaffold showed BMP2 expression for a much longer time (more than 28 days) compared with the single axial electrospun scaffold, as evaluated by qRT-PCR and western blot after culturing with hPDLSCs. These results suggested that the core-shell PEI/pBMP2-PLGA scaffold fabricated by coaxial electrospinning had a good gene release behavior and showed a prolonged expression time with a high transfection efficiency.